Dynamics of Communication and Social Conflict in Coastal Communities of Southern Jember Regency, East Java Indonesia - Sunartomo, Aryo Fajar; Sofia; Lenny Luthfiyah (Technium Social Sciences Journal, 2026)
The southern coastal area of Jember Regency, East Java Province is a region where the majority of the population depends on the marine fisheries sector. The main livelihoods include capture fisheries, small-scale fish processing home industries, and tourism-related activities. Communication dynamics and social conflicts emerge alongside population growth, economic development, and changes in the region’s carrying capacity, as well as the emergence of new areas in trade, industry, and tourism sectors. In addition, southern coastal communities are also facing pressure due to declining capture fisheries yields caused by seasonal changes. This study aims to examine the dynamics of communication and social conflict within southern coastal communities. Communication among community members at various levels of social relations gives rise to group communication patterns rooted in socio-cultural systems and pre-existing communication networks. The presence of verbal and non-verbal symbols in symbolic communication not only reflects the internalization of values within individuals but also represents existing social stratification. The forces operating within the dimension of symbolic communication remain an important measure in social interactions that are deeply embedded in collectively upheld norms and values. The ongoing dynamics of communication within the community generate issues related to cultural diversity, including the emergence of conflicts among individuals in coastal communities. These conflicts are driven by competition, role domination, and differences in values upheld by individuals occupying different social roles in the southern coastal communities of Jember Regency. Such conflicts primarily occur within the dimension of interpersonal communication. Interpersonal communication emerges when message exchange activities take place in various forms of interaction involving individuals, particularly when mismatched interpretations arise between two or more parties engaged in the interaction.